Gaya Kepemimpinan Demokratis Direktur Rumah Sakit terhadap Kedisiplinan Karyawan - Fadilla Delima Sandi; Nyoman Anita Damayanti (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2021)
This study aims to determine the effect of the democratic leadership style of the hospital director on the discipline of the employees of RSU DR Moedjito Dwidjosiswojo. This research method uses a survey method carried out by collecting data through a questionnaire (questionnaire). The results showed three leadership styles at Dr. Moedjito Dwidjosiswojo General Hospital, 6 with SD 0, democracy with 21 points with 5 SD, and accessible 1 with 1 SD. In conclusion, Dr. Moedjito Dwidjosiswojo's director's democratic leadership style influenced employee discipline with no evidence. Undisciplined employees based on predetermined work hours. Keywords: Leadership Style, Employee Discipline